ChemInform Abstract: Copper‐Mediated Oxidative Trifluoromethylthiolation of Aryl Boronic Acids with CF3CO2Na and Elemental Sulfur. Issue 17 (28th April 2014) - Zhai, Lijuan; Li, Yaming; Yin, Jun; Jin, Kun; Zhang, Rong; Fu, Xinmei; Duan, Chunying
Abstract Inexpensive sodium trifluoroacetate and elemental sulfur are employed as reagents to access aryl trifluoromethyl thioethers through an oxidative decarboxylative pathway.